Adult ovarian granulosa cell tumors: analysis of outcomes and risk factors for recurrence. Issue 5 (9th February 2023) - Plett, Helmut; Ricciardi, Enzo; Vacaru, Vlad; Ramspott, Jan Philipp; Colombo, Nicoletta; Sehouli, Jalid; du Bois, Andreas; Garbi, Annalisa; Richter, Rolf; Ataseven, Beyhan; Aletti, Giovanni; Braicu, Elena; et al.
Abstract : Objective: Adult granulosa cell tumors represent less than 5% of all ovarian malignancies. The aim of this study was to analyze the clinicopathological parameters and their impact on progression-free and overall survival. Methods: Patients with primary adult granulosa cell tumors treated in three international referral centers between July 1999 and December 2018 were included. The following data were anonymously exported from the prospective database: age at diagnosis, International Federation of Gynecology and Obstetrics (FIGO) stage, adjuvant therapy, surgical procedures, progression-free survival, and overall survival. Descriptive statistical analysis regarding tumor and treatment characteristics was performed. Survival analyses included Kaplan–Meier functions and Cox proportional hazard ratios (HR). Results: A total of 168 patients with primary adult granulosa cell tumors were included. Median age was 50 years (range 13–82). With regard to stage distribution, 54.2% (n=91) of patients were FIGO stage IA, 1.2% (n=2) were stage IB, 26.8% (n=45) were stage IC, and 17.9% (n=30) were FIGO stage II–IV. 66.7% (n=112) of patients underwent surgical restaging, of whom 17.9% (n=20) were moved to a higher stage. In addition, 36 (21.4%) patients underwent fertility-sparing surgery. After a median follow-up of 61 months (range 0–209), 10.7% of patients (n=18) had recurrent disease and 4.8% (n=8) died of disease. Five-year progression-free survival was 86.1% and estimated overall survival was 95.7%. Five-year progression-free survival was worse for patients with advanced stages (FIGO stage IA/B vs IC: HR 5.09 (95% CI 1.53 to 16.9); FIGO stage IA/B vs II–IV: HR 5.62 (95% CI 1.58 to 19.9)). Nineteen patients receiving adjuvant chemotherapy had lower estimated 5-year progression-free survival compared with patients not receiving chemotherapy (49.7% vs 91.1%, p<0.001; HR 9.15 (95% CI 3.62 to 23.1)). Conclusion: The prognosis of patients with primary adult granulosa cell tumors is mainly determined by FIGO stage. The outcome of patients with FIGO stage IC is comparable to those with advanced stages. Fertility-sparing surgery seems to be a safe procedure in stage IA. Our data do not support the use of adjuvant chemotherapy in early and advanced stages of adult granulosa cell tumors.